First record of Palaeostomocystis subtilitheca in Holocene marine sediments from the Beagle Channel, southern Tierra del Fuego, Argentina - Candel, Maria Soledad (Review of Palaeobotany and Palynology)
This study documents the occurrence of Palaeostomocystis subtilitheca in Holocene sediments from the Beagle Channel area, southern Argentina, and represents the first record of this acritarch in high latitudes of Southern Hemisphere. Palaeostomocystis subtilitheca is considered as an indicator for polar to subpolar environments with high planktonic productivity and nutrient-rich waters, and can probably be associated with low-salinity stratiﬁed waters. The Beagle Channel presents environmental characteristics similar to those reported by other authors in Central West Greenland and the Faroe Islands, characterized by high concentrations of nutrients in the surface waters. The Beagle Channel constitutes a favourable environment for the development of this species in subpolar regions of the Southern Hemisphere. Fil: Candel, Maria Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina